APAKAH PENGGUNAAN TEKNOLOGI INFORMASI DALAM E-COMMERCE MEMENGARUHI FONDASI BISNIS? - Marchianto, Rifki Fitri Arif; Endro, Gunardi (Journal of Entrepreneurship, Management and Industry (JEMI), 2018)
As e-commerce has been considered a part of lifestyle, this reserach aims to prove whether the use of information technology influences or enriches the foundation of business. The research used a simple linear regression statistical method with a sample taken from Lazada Indonesia's online business consumers. If it were proven, the variables that represent the quality of the use of information technology would affect the variable of e-customer satisfaction. The result was in fact not proven. The variable of e-customer satisfaction was statistically affected by variables that represent the foundation of business only, namely security and fairness in transactions. Thus the use of information technology in e-commerce does not affect the foundation of business. The result suggests that the right online business strategy is a strategy that focuses on increasing the perceived  security and fairness in transactions through the development of features in the use of online technology.